2022
DOI: 10.1002/1878-0261.13218
|View full text |Cite
|
Sign up to set email alerts
|

miR‐126 downregulates CXCL12 expression in intestinal epithelial cells to suppress the recruitment and function of macrophages and tumorigenesis in a murine model of colitis‐associated colorectal cancer

Abstract: Inflammatory bowel disease, characterised by chronic relapsing‐remitting colitis, is a significant risk factor for colorectal cancer (CRC). Previously, we showed that miR‐126 functions as a tumour suppressor in CRC and is inversely correlated with tumour proliferation, metastasis and patient prognosis. In the current study, we documented a protective role for miR‐126 in colitis‐associated CRC (CAC) and its underlying mechanism. We detected downregulated miR‐126 expression during colorectal tumorigenesis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
2
8
0
Order By: Relevance
“…MiR-126 has been reported downregulated in in ammatory diseases [24,25], and it was detected in human periodontal diseased gingival tissues differing from healthy gingival tissues [44]. Overexpression of MiR-126 decreased the expression of interleukin (IL)-1β [45], IL-6 and TNFα [46], and these studies were consistent with the results of our experiments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MiR-126 has been reported downregulated in in ammatory diseases [24,25], and it was detected in human periodontal diseased gingival tissues differing from healthy gingival tissues [44]. Overexpression of MiR-126 decreased the expression of interleukin (IL)-1β [45], IL-6 and TNFα [46], and these studies were consistent with the results of our experiments.…”
Section: Discussionsupporting
confidence: 91%
“…MiR-126 is considered as one of the transcriptional regulators of the periodontitis-related mediators [21][22][23]. In various models of in ammation, upregulation of miR-126 has been shown to be bene cial in reducing the recruitment of macrophages and inhibiting in ammation [24,25]. Thus targeted delivery of miR-126 to macrophages may provide an effective immunomodulatory strategy for the treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exosomal transfer of miRNA from CXCR4-overexpressing colorectal cancer cells to tumor-associated macrophages was shown to enhance their M2 polarization and metastasis-promoting characteristics [ 247 ]. In contrast, in a murine model of colitis-associated colorectal cancer, miR-126 (which was downregulated in patients with colorectal cancer) reduced CXCL12 expression in intestinal epithelial cells functioning as a tumor suppressor by inhibiting the recruitment and function of macrophages [ 248 ]. In colorectal cancer, it is however clear that the CXCL12-CXCR4/ACKR3 axis itself has tumor- and metastasis-promoting effects, which were recently reviewed by Goïta et al [ 249 ].…”
Section: The Homeostatic and Inflammatory Chemokine Cxcl12mentioning
confidence: 99%
“…Artificial over-expression of miR-126 in colon cancer cells led to the inhibition of cell viability, cell migration and invasion capacity [ 49 ]. Even in mice, it was shown that miR-126 exhibits an anti-tumour effect by activating macrophages and altering the proliferation and the migration of tumour cells [ 50 ]. These findings indicate that down-regulation of miR-126 in tissue is correlated with cancer development.…”
Section: Discussionmentioning
confidence: 99%